Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ca.23877
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism influence on lumbar intervertebral disc degeneration

Abstract: Intervertebral disc (IVD) degeneration is a multifaceted pathology that is the main morphological cause of lower back pain. This study aimed to determine the link between the vitamin D receptor gene single nucleotide polymorphisms (SNPs) and degenerative processes of the lumbar spine. The complete lumbar spinal columns were collected from 100 Caucasian cadavers via ventral dissection. The specimens for the histological analysis were harvested from the L5/S1 IVDs and endplates.Then, the tissues were cut into sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been reported that vitamin D is closely associated with rickets [ 2 ], osteoarthritis [ 3 ], osteoporosis [ 4 ] and lumbar disc herniation [ 5 , 6 ]. The vitamin D receptor (VDR) is widely expressed in intervertebral disc cells, and in various studies, genetic polymorphisms, such as TaqI (rs731236), FokI (rs2228570), and ApaI (rs7975232), have been implicated in the pathogenesis of IVDD [ 7 , 8 ]. The association between vitamin D and degenerative disc disease is strong, as it has been demonstrated in large groups with diverse ethnic backgrounds, including Australian, British, Chinese, Japanese and Finnish populations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that vitamin D is closely associated with rickets [ 2 ], osteoarthritis [ 3 ], osteoporosis [ 4 ] and lumbar disc herniation [ 5 , 6 ]. The vitamin D receptor (VDR) is widely expressed in intervertebral disc cells, and in various studies, genetic polymorphisms, such as TaqI (rs731236), FokI (rs2228570), and ApaI (rs7975232), have been implicated in the pathogenesis of IVDD [ 7 , 8 ]. The association between vitamin D and degenerative disc disease is strong, as it has been demonstrated in large groups with diverse ethnic backgrounds, including Australian, British, Chinese, Japanese and Finnish populations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic modulations associated with human disc degeneration or back pain are separated by gene function, such as structural enzymes that cleave extracellular-matrix molecules and inflammatory mediators [ 37 ]. In fact, many SNPs have been reported in several studies to be associated with IVDD, such as MMP1 and MMP3 in the degeneration of different matrix components [ 38 ]; COL1, 2, 9, and 11 in the degradation or loss of collagen [ 33 , 39 , 40 , 41 , 42 ]; VDR and CLIP in the degradation or loss of proteoglycan [ 43 , 44 ]; and IL-1, IL-6 and COX2 in the increase of inflammation [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%